Teenagers, Literacy and School - Cruickshank, Ken (Taylor & Francis, 2006)
This unique and timely book follows the experiences of four Arabic teenagers, their families and their community, focusing on the role of literacy in their daily lives and the differences between home and school. The author looks at the conflict between expectations and practices at school and in the home, arguing that problems are inevitable where class and cultural differences exist. Emerging themes include: how literacy practices in the community are undergoing rapid change due to global developments in technology how the patterns of written and spoken language in Eng and Arabic in the home are linked with social practices in logical and coherent ways how many of the family practices that differ from school culture and language become marginalised. Built around these insightful case studies yet grounded in theory, this book is of immediate relevance to teachers working in multicultural contexts and students and lecturers in language/literacy or on TESOL courses.